2016
DOI: 10.4103/ijmr.ijmr_1447_14
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia as a non-invasive index of ′brain-heart′ interaction in stress

Abstract: Respiratory sinus arrhythmia (RSA) is accepted as a peripheral marker of cardiac-linked parasympathetic regulation. According to polyvagal theory, the RSA is also considered as the index of emotion regulation. The neurovisceral integration model posits that parasympathetic modulation of the heart marked by RSA is related to complex nervous regulation associated with emotional and cognitive processing. From this perspective, high resting RSA amplitude associated with a greater withdrawal during stressors and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 80 publications
0
9
0
1
Order By: Relevance
“…Furthermore, respiratory sinus arrhythmia is characterized by heart rate variability in response to respiration. It is also accepted as a peripheral marker of cardiac-linked parasympathetic regulation, and as the index of emotion regulation [ 70 ]. Also, stress level and physical activity level must be considered along with HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, respiratory sinus arrhythmia is characterized by heart rate variability in response to respiration. It is also accepted as a peripheral marker of cardiac-linked parasympathetic regulation, and as the index of emotion regulation [ 70 ]. Also, stress level and physical activity level must be considered along with HRV.…”
Section: Discussionmentioning
confidence: 99%
“…This theory stresses the importance of autonomic functions in regulating human behavior in normal and abnormal conditions. The vagus nerve originates into two different nuclei of the brainstem: the Dorsal Motor Nucleus of the vagus (DNMX) and the Nucleus Ambiguus (NA), each of them ending in the sinoatrial node, but only NA having the control of respiratory sinus arrhythmia (RSA) which is an index of cardiac vagal modulation, and it is associated with emotion regulation (ER) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is note-worthy that cardiac vagal control is associated with emotion and social cognitive regulation. Specifically, higher resting cardiac vagal modulation provides better cognitive control and, in contrast, reduced cardiovagal regulation can be associated with maladaptive cognitive and emotional regulation [19,[41][42][43][44]. Our previous studies have demonstrated lower cardio-vagal regulation in different diseases associated with emotional and cognitive dysregulation such as depression [23,45] or attention deficit/hyperactivity disorder -ADHD [46,47,22].…”
Section: Discussionmentioning
confidence: 99%